Implementation of Outsourcing Employee Sales System For Verification and Acceleration Salary Transparency - Ruli Supriati; Junaidi Junaidi; John Hendri (Universitas Raharja, 2020)
The high graduation rate makes many private agencies build a company engaged in outsourcing. This requires the existence of a system that supports the process of managing technology-based resources. In practice the payroll process is still done manually, starting from the calculation of attendance to printing invoices sent to clients and this causes a delay in invoicing billing, thereby reducing the productivity of the company itself to grow and develop. With these problems the author feels the need to make an application using several methods such as the process of data analysis, design, which includes usecase diagrams, activity diagrams, sequence diagrams, class diagrams. So that it is expected to be able to produce a payroll system that is effective and efficient and fast and accurate. The payroll system that is designed, can be used to manage employee data, work, holidays, overtime, deductions and benefits that have been determined based on data that has been input and is also used to print invoice reports, salary slips. Finally with the existence of this payroll system, the salary calculation process can be done automatically without counting manually and salary data can be received accordingly, with notes that all data input is valid.